'Workshop for Nagoya Protocol and Plant Treaty National Focal Points in Latin America and the Caribbean’ - Ellis, David; Gullotta, G.; Halewood, Michael; Argumedo, A.; Garforth, K.; Toledo, A. (2019)
The capacity-building Workshop for National Focal Points in Latin America and the Caribbean on Mutually Supportive Implementation of the Nagoya Protocol and the International Treaty on Plant Genetic Resources for Food and Agriculture, was held 25-28 September 2018 at the International Potato Center (CIP), Lima, Peru. The workshop was attended by over 60 participants, including National Focal Points for the Nagoya Protocol to the Convention on Biological Diversity and the International Treaty on Plant Genetic Resources (CBD) for Food and Agriculture (Plant Treaty), from 16 countries in Latin America and the Caribbean. The workshop was also attended by representatives from the Secretariats of the Plant Treaty and CBD, the International Seed Federation, farmer and indigenous peoples organizations, national and international agricultural research organizations and experts from the region who have been working for decades on access and benefit-sharing policy issues. The objectives of the workshop were to: 1. Strengthen network ties between National Focal Points within each country and across the regions; 2. Analyse challenges and opportunities for implementing the Plant Treaty and the Nagoya Protocol in a mutually supportive manner, and in ways that advance complementary policy goals, such as climate change adaptation, and improving the livelihoods of indigenous peoples and local communities; 3. Equip participants with tools to help address ‘real life’ scenarios where mutually supportive implementation is important, and 4. Identify the kinds of additional support that countries need to implement the Plant Treaty and Nagoya Protocol in mutually supportive ways.